Chapter Interventi di tutela e valorizzazione della biodiversità del SIC "Torre dell'Orso"- IT 9150004 - Rugge, Cristina (Proceedings e report, 2020)
The project for the enhancement of the SIC IT9150004 (POR Puglia 2014/2020 Axis VI Environmental protection and promotion of natural and cultural resources - Interventions for the protection and enhancement of terrestrial and marine biodiversity) involves the enhancement of the Brunese Canal which makes it a fundamental infrastructure through the upgrading of the waterway, the coordination between environmental and rural development policies, the redevelopment and recovery of the landscape of its compromised areas together with the reduction of the pollution and the consequent improvement in the quality of the water poured into the sea.